Assessing concussion knowledge among students with varying levels of sports involvement - Willy Cheung; Ekaterina Tangog; Derek Wang; Ellese Lupori; Fatima Iqbal; Juan R. Ramirez; Lauren McKay; Travis Alsky; David Baron (Hogrefe AG, 2024)
Abstract: Introduction/Purpose: Many medical and physical therapy students indicate that their source of concussion knowledge stems from previous involvement in sports; they also expressed that their education may not prepare them to manage patients with concussions. This study aims to examine how involvement in sports informs concussion knowledge, and to identify gaps in knowledge. Methods: A 17-question Qualtrics survey was distributed to allopathic and osteopathic medical and physical therapy students. Participants were asked to self-report their concussion history, rank their confidence regarding concussion knowledge, answer objective knowledge questions, and assess the degree to which concussion education was taught and its relevance to their field. ANOVA and Chi-square tests were used for analysis. Results: Students with sports participation at the college and professional level demonstrated higher self-ranked concussion knowledge and higher performance on concussion knowledge questions. Our study also showed that deficits in concussion management exist. Conclusion: Students with college or professional sports involvement consistently performed better on survey questions due to their higher rates of personal experience, though the majority of students surveyed did not have this level of sports experience and its accompanying exposure to concussion. Effect sizes for significant results were relatively small, suggesting that practical applications may be limited. Therefore, involvement in sports should not be recognized as an adequate source of concussion education for future clinicians. Based on our results, it can be suggested that all medical and physical therapy students, regardless of sports involvement, will benefit from having a structured curriculum focused on concussion education.